Pengembangan Bahan Ajar E-Comic melalui Aplikasi Canva pada Mata Pelajaran IPAS di Sekolah Dasar - Shahwa, Diva Nadiyatus; Mustamiroh, Mustamiroh; Iksam, Iksam (SITTAH: Journal of Primary Education, 2024)
This research is motivated by the lack of variety of science teaching materials used by fifth-grade teachers and the minimal number of teaching materials, as well as the fact that there are still teachers who are not skilled in utilizing ICT in making teaching materials. This study aimed to determine the development process and feasibility of open materials based on E-Comic. The research method used is Research and Development (R&D) with the ADDIE model. The study results are 1) Development of E-Comic-based teaching materials using the ADDIE model through 5 stages: analysis, design, development, implementation, and evaluation. The process of developing teaching materials is carried out by analyzing student needs, characteristics, and curriculum, making plans such as storyboard design, material plans, and product design plans including character and cover designs using the AI-assisted Canva application. 2) The results of the feasibility test by media experts 1 and 2 scored 86% and 90% with the category "Feasible". The feasibility test results by material experts 1 and 2 scored 84% and 98% with the category "Feasible". The final stage was a field trial and then an evaluation was carried out with product revisions. Teacher response test, student responses in small and large groups scored 95%, 88%, and 87.2% with the category "Appropriate". It can be concluded that E-Comic-based teaching materials are appropriate for use in learning for students at school.